Studi Agama & Etika Islam dan Keberagamaan Mahasiswa "Z" Generation: Kajian di Lingkungan Kampus ITB Bandung - Yedi Purwanto; Shohib Khoiri (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
Time is going on so fast, demanding man to have the quality and the courage to compete. The competition was sometimes make people forget the norm. To solve this problem it is required religion as a way of life. The method used herein are reviewing the literature and system of Islamic religious education activities in Bandung Institute of Technology (ITB). The findings of this study stated that the First, religious education in public universities is needed to foster the spirituality of the younger generation. Second, "Z" generation is the object of da'wah who are very close to IT (information technology), so there must be a specific design of da’wa which is meeting their need. Third, the role of Salman mosque is very central in implementing any Islamic da'wa to the students of ITB.